Diseño de Indumentaria Urbana Sostenible a partir de la incorporación de Fibras Vegetales - Jocelyn Abigail, Valle Bustillos (2023)
This executive summary presents the key aspects of a thesis focused on sustainable urban apparel design using vegetable fibers. The main objective of this study is to explore the possibilities and benefits of using alternative vegetable fibers in the urban fashion industry to promote more sustainable and environmentally friendly practices. The methodology used was design thinking, which allows to divide it into different phases where fundamental aspects of product innovation from a real need are detailed. The study is based on extensive bibliographic research and analysis of case studies. Data was collected on the properties of vegetable fibers, their availability, sustainable production processes, and the environmental and social benefits associated with their use. The results reveal that by using both traditional and alternative vegetable fibers, the products have an added value due to their properties such as being renewable, and biodegradable, and at the same time these fibers require less water and energy resources compared to synthetic or animal fibers. In addition, their production can positively impact local communities and promote sustainable agricultural practices. In summary, this study provides an industry-wide view. The findings show the potential of these fibers to transform the fashion industry towards more responsible and environmentally friendly practices. This work contributes to the understanding and promotion of sustainable fashion, providing a solid foundation for future research and action in this area.